Promoting girls in sport - (Still) in keeping with the times? - Elke Gramespacher (Bern Open Publishing, 2024)
Introduction "Promoting girls in sport": How to find an interview partner for this topic? In their search, the editors of the Swiss girls' magazine 'KALEIO - For Girls (and the Rest of the World)' learnt that the topic is 'out'. But although we see more and more equalization of sport-related behavior (e.g., Hartmann-Tews, 2009), promoting girls in sport still makes sense. Methods The results stem firstly from an overview article, in which international findings were summarized. Secondly, data come from reanalyzes of two representative MOBAK studies, where children were measured by gender-neutral MOBAK-tests and parents were questioned about their children's physical activity behaviors. Results The overview article (Adler & Gramespacher, 2021) compiled international findings on the activity behavior of girls and boys during the transition from kindergarten to grade one. The studies available report on gender-stereotypical behavior of children - and girls stand out here in different ways. Further evidence of gender-stereotypical behavior can be shown by reanalysis of MOBAK-data with 1st graders (Gramespacher et al., 2022) and 3rd graders (Gramespacher et al., in press): Overall, reanalyzed MOBAK-data show, that there is a difference in basic motor competencies that might be explained by gender-stereotype sport socialization - and this clearly is a disadvantage for the girls in some motor competencies. Discussion/Conclusion Presented data point out the still existing need for action in promoting girls in sport. We must discuss the complexity associated with the promotion of girls in all fields of sport and in this realm, we must define specific goals of promoting girls in sport (e.g., Kugelmann, 2002). But in future, we should consider the role of differentiation in research and sports practice: Shouldn't we differentiate in general for all different types of learners without classifying? References Adler, K., & Gramespacher, E. (2021). Mädchen im Fokus: Kindliches Aktivitätsverhalten im Übergang Kindergarten - Schule [Focus on girls: Children's activity behaviour in the transition from kindergarten to school]. In K. Adler & C. Andrä (Eds.), Bewegung, Spiel und Sport bei Kindern im Krippen- und Kindergartenalter. Forschung aus der Praxis für die Praxis (pp. 278-304). Universitätsverlag Chemnitz. Gramespacher, E., Herrmann, C., Ennigkeit, F., Heim, C., & Seelig, H. (in press). Geschlecht - ein Prädiktor für motorische Basiskompetenzen. Eine Studie mit MOBAK-Daten von Drittklässler*innen [Gender - A predictor of basic motor skills. A study with MOBAK data from third graders]. In C. Herrmann, F. Ennigkeit & H. Seelig (Eds.), Motorische Basiskompetenzen: Konstrukt, Forschungsstand und Anwendung. Springer VS. Gramespacher, E., Herrmann, C., & Seelig, H. (2022). Geschlechtsbezogenes Sportengagement - ein Prädiktor für motorische Basiskompetenzen. Eine Analyse mit Daten von Erstklässler*innen [Gender-related sport engagement - A predictor of basic motor skills. An analysis with data from first graders]. In G. Sobiech & E. Gramespacher (Eds.), Wir und die Anderen. Differenzkonstruktionen in Sport und Schulsport (Vol. 295, pp. 47-56). Feldhaus. Hartmann-Tews (2009). Sportentwicklung und Inklusion aus Geschlechterperspektive [Sport development and inclusion from a gender perspective]. In E. Balz & D. Kuhlmann (Eds.), Sportentwicklung. Grundlagen und Facetten (pp. 65-75). Meyer & Meyer. Kugelmann, C. (2002). Geschlechtssensibel unterrichten - Eine sportdidaktische Herausforderung [Gender-sensitive teaching - A challenge in sports didactics]. In C. Kugelmann & C. Zipprich (Eds.), Mädchen und Jungen im Sportunterricht (Vol. 125, pp. 11- 20). Feldhaus.